Acculturation Of Islamic Values And Local Culture: A Semiotic Analysis Of Symbols And Rituals In The Sekura Festival Tradition In West Lampung - Sri Fatmawati; Machfudz Fauzi; Rahmat Hidayat (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2025)
The Sekura Festival custom in West Lampung is one of the many fascinating acculturation phenomena that Indonesia has to offer, given its rich cultural heritage and predominately Muslim populace. However, as modernization advances, traditions may lose their relevance. Because of this, people may view these customs as merely amusement without appreciating the Islamic principles they represent. There will be a conflict between adhering to Sharia principles and preserving culture as a result. Examining how Islamic ideals are represented in the symbols and customs of the Pesta Sekura tradition practiced by the residents of West Lampung is the aim of this study. Relevant literature content analysis was used to perform library research. According to the study's findings, the Sekura Festival is full of Islamic principles that are internalized through seven key elements: friendship (ukhuwah islamiyah), thankfulness, tolerance and cooperation (ta'awun), joy within the bounds of Sharia law, education and cultural da'wah, simplicity and unity, peace and reconciliation, and gratitude. Sekura symbols (Betik and Kamak) and the ritual system as a whole are excellent means of conveying these principles. According to this study, the Sekura Festival is a tangible illustration of cultural da'wah (dakwah bil hikmah), which is the integration of Islam with regional culture while adhering to Sharia law. In the face of modernity's problems, it is also a crucial means of preserving cultural legacy and fortifying the community's Islamic identity.